2007
DOI: 10.1111/j.1528-1167.2007.00919.x
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Onset and Propagation of ECT‐induced Seizures

Abstract: Summary:Purpose: Regions of seizure onset and propagation in human generalized tonic-clonic seizures are not well understood. Cerebral blood flow (CBF) measurements with single photon emission computed tomography (SPECT) during electroconvulsive therapy (ECT)-induced seizures provide a unique opportunity to investigate seizure onset and propagation under controlled conditions.Methods: ECT stimulation induces a typical generalized tonic-clonic seizure, resembling spontaneous generalized seizures in both clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
56
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(64 citation statements)
references
References 42 publications
4
56
0
4
Order By: Relevance
“…SPECT studies of ECT-induced seizures in depression patients have revealed significant CBF decreases in the bilateral anterior and posterior cingulate gyrus and precuneus [7,21] in addition to decreases in the medial frontal and lateral parietal lobes [9]. These findings were largely recapitulated in a subsequent study of a large group of epilepsy patients, which reported ictal and post-ictal CBF decreases in the precuneus and cingulate gyrus and postictal CBF decreases in the lateral frontoparietal association cortex [14].…”
Section: Default Mode Network Involvement In Generalized Tonic-clonicsupporting
confidence: 57%
See 2 more Smart Citations
“…SPECT studies of ECT-induced seizures in depression patients have revealed significant CBF decreases in the bilateral anterior and posterior cingulate gyrus and precuneus [7,21] in addition to decreases in the medial frontal and lateral parietal lobes [9]. These findings were largely recapitulated in a subsequent study of a large group of epilepsy patients, which reported ictal and post-ictal CBF decreases in the precuneus and cingulate gyrus and postictal CBF decreases in the lateral frontoparietal association cortex [14].…”
Section: Default Mode Network Involvement In Generalized Tonic-clonicsupporting
confidence: 57%
“…SPECT studies have revealed that the earliest increases are often in the temporal lobe, where tonic-clonic seizures most commonly originate [14,68]. Additionally, large CBF increases during the generalization phase have been observed in the bilateral medial and lateral parietal cortex [9,21] as well as in the thalamus, basal ganglia, and superior medial cerebellum [9,14,21]. Interestingly, we recently observed that during the post-ictal phase, CBF in the bilateral lateral cerebellar hemispheres continues to increase before returning to a baseline level [14].…”
Section: Default Mode Network Involvement In Generalized Tonic-clonicmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, single photon emission computed tomography (SPECT) is par ticularly well suited to the investigation of rCBF during seizures. A collaboration among neurolo gists and psychiatrists at Yale University School of Medicine suggested hypotheses to explain both the reduced clinical efficacy of right unilateral ECT and the reduced effect on verbal memory (Enev 2007). It would have been informative to compare threshold right unilateral ECT with threshold bilateral ECT, but threshold right unilateral ECT was not included.…”
Section: The Reconciliation Of Apparently Divergent Findingsmentioning
confidence: 99%
“…Bilateral ECT produced robust increases of blood flow symmetrically in frontal and temporal regions of the brain. In right unilateral ECT, the relative sparing of the left temporal lobe was the likely explanation of the reduced impair ment of verbal memory, and the relative sparing of the left cortical and subcortical regions was the likely explanation of the reduced clinical efficacy (Enev 2007). More will be said about the putative neuroanatomy of major depression below.…”
Section: The Reconciliation Of Apparently Divergent Findingsmentioning
confidence: 99%